2006
DOI: 10.1038/sj.mp.4001888
|View full text |Cite|
|
Sign up to set email alerts
|

n-3 Polyunsaturated fatty acid deprivation in rats decreases frontal cortex BDNF via a p38 MAPK-dependent mechanism

Abstract: Decreased docosahexaenoic acid (DHA) and brain-derived neurotrophic factor (BDNF) have been implicated in bipolar disorder. It also has been reported that dietary deprivation of n-3 polyunsaturated fatty acids (PUFAs) for 15 weeks in rats, increased their depression and aggression scores. Here, we show that n-3 PUFA deprivation for 15 weeks decreased the frontal cortex DHA level and reduced frontal cortex BDNF expression, cAMP response element binding protein (CREB) transcription factor activity and p38 mitoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(169 citation statements)
references
References 91 publications
(108 reference statements)
11
151
1
3
Order By: Relevance
“…Our previous study has indicated possible involvement of intracellular PLA 2 s (probably iPLA 2 ) and release of long chain fatty acids in the mouse prefrontal cortex after chronic antidepressant treatment (Lee et al 2009). It is possible that treatment modalities of depression may involve the induction of PLA 2 isoforms to endogenously release long chain fatty acids such as DHA, which have antidepressant effects (DeMar et al 2006;Rao et al 2007). Interestingly, many of the lipid changes in the striatum were opposite to that of the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has indicated possible involvement of intracellular PLA 2 s (probably iPLA 2 ) and release of long chain fatty acids in the mouse prefrontal cortex after chronic antidepressant treatment (Lee et al 2009). It is possible that treatment modalities of depression may involve the induction of PLA 2 isoforms to endogenously release long chain fatty acids such as DHA, which have antidepressant effects (DeMar et al 2006;Rao et al 2007). Interestingly, many of the lipid changes in the striatum were opposite to that of the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…As ERKs also play a role in cytoskeletal polymerisation, these findings may be related to structural hippocampal differences between SAL and LAL such as the intra-and infrapyramidal mossy fibres [42]. Also relevant are findings from Rao et al (2007) who showed that in rats dietary deprivation of certain polyunsaturated fatty acids led to increases in aggression and depression together with, among others, reductions in frontal cortex BDNF expression and p38 MAPK activity [43].…”
Section: Identification Of Biological Pathways Associated With Aggresmentioning
confidence: 93%
“…There are numerous studies indicating that ROS induced neuronal damage has an important role in the pathophysiology of depression, probably via membrane omega 3 polyunsaturated fatty acids (PUFAs) pathology [8,9], decreasing activity of GSH-Px, catalase and superoxide dismutase (SOD) [3], and antioxidant vitamin [10], suggesting oxidative damage. Although most of the oxygen used in brain tissue is converted to CO 2 and water, small amounts of oxygen forms ROS.…”
Section: Introductionmentioning
confidence: 99%